Disease control and disease activity in hereditary angioedema: two sides of the same coin? - Heibati, Behzad; Borle, Jack; Ritchie, Bruce; Adatia, Adil (Frontiers in Immunology, 2025)
BackgroundHereditary angioedema (HAE) is a genetic disorder characterized by episodic subcutaneous and submucosal swelling. Patient-reported outcome measures (PROMs) are recommended for routine clinical assessment by international guidelines and are used as secondary outcome measures in pivotal clinical trials for novel investigational drugs. The Angioedema Control Test (AECT) and Hereditary Angioedema Activity Score (HAE-AS) are validated tools designed to aid in HAE patient assessment, but the extent to which they measure different disease outcomes is unclear. The aim of this study was to examine how these measures correlate and inform clinical practice.MethodsWe conducted a retrospective study of patients with HAE types 1 and 2 at the Edmonton Angioedema Center of Reference and Excellence. AECT and HAE-AS scores were obtained from patient-completed questionnaires during routine visits. Multiple linear regression was used to examine the association between HAE-AS and AECT scores with age, sex, and long-term prophylaxis (LTP) status as predictors. Receiver operating characteristic (ROC) analysis was used to determine the optimal HAE-AS score cutoff that predicts poor disease control as determined by the AECT.ResultsThere were 25 participants included with a mean age of 39.4 years (SD = 13.7), 72% of whom were female. Most had HAE Type 1 (76%) and 52% were receiving LTP. SC C1-inhibitor therapy was the most common LTP (36%). Most had well managed disease with a median AECT score of 11.88 (range: 5-16) and HAE-AS of 5.84 (range: 0-13). A statistically significant but weak negative correlation was found between AECT and HAE-AS (β=−0.67, p=0.002). ROC analysis showed that an HAE-AS score >5 had a sensitivity of 100% and specificity of 61% for poor disease control.ConclusionsThe AECT and HAE-AS instruments are weakly correlated, indicating that they provide related but distinct information to the practicing clinician. Using both AECT and HAE-AS in clinical practice can thus provide a more comprehensive patient evaluation.